Study of the antitumour effects and the modulation of immune response by histamine in breast cancer - Nicoud, Melisa Beatriz (2020)
Background: The aim of this work was to improve the knowledge of the role of histamine in breast cancer by assessing the therapeutic efficacy of histamine and histamine H4 receptor (H4R) ligands in a triple-negative breast cancer (TNBC) model developed in immunocompetent hosts. By using publicly available genomic data, we further investigated whether histidine decarboxylase (HDC) could be a potential biomarker. Methods: Tumours of 4T1 TNBC cells were orthotopically established in BALB/c mice. Treatments employed (mg kg−1): histamine (1 and 5), JNJ28610244 (H4R agonist, 1 and 5) and JNJ7777120 (H4R antagonist, 10). Results: Increased HDC gene expression is associated with better relapse-free and overall survival in breast cancer patients. Histamine treatment (5 mg kg−1) of 4T1 tumour-bearing mice reduced tumour growth and increased apoptosis. Although no immunomodulatory effects were observed in wild-type mice, significant correlations between tumour weight and cytotoxic lymphocyte infiltration were detected in H4R knockout mice. H4R agonist or antagonist differentially modulated tumour growth and immunity in 4T1 tumour-bearing mice. Conclusions: Histamine plays a complex role and stands out as a promising drug for TNBC treatment, which deserves to be tested in clinical settings. HDC expression level is associated with clinicopathological characteristics, suggesting a prognostic value in breast cancer.